PENGARUH KUALITAS PRODUK DAN KERAGAMAN PRODUK TERHADAP KEPUASAN PELANGGAN PADA PT LKD MULTI INDUSTRI DI KOTA BATAM - Tan, Vially; Saputra, Asron (SCIENTIA JOURNAL, 2021)
This research is intended to research the impact of product quality (X1) and product diversity (X2) on customer satisfaction (Y) at PT LKD Multi Industri in Batam city. The analytical method used in this research is using quantitative analysis and using questionnaires to obtain data. The population in this research were customers of PT LKD Multi Industri in Batam City, of which 120 customers. The sampling technique which used is the Non-probability sampling technique which uses saturated sampling with a sample of 120 customers of PT LKD Multi Industri. Furthermore, the collected data were analyzed using multiple Linear regression analysis and hypothesis testing to establish the effect of product quality and product diversity on customer satisfaction at PT LKD Multi Industri with the help of version 25 of the SPSS (Statistical Package for the Social Sciences) calculating tool. that Product quality variable (X1) partially has a positive and significant effect on customer satisfaction variables (Y) and product diversity variables (X2) partially has a positive and significant effect on the customer satisfaction variable (Y). Simultaneously, product quality (X1) and product diversity (X2) has a positive and significant effect on customer satisfaction (Y) at PT LKD Multi Industri in Batam City.